2019
DOI: 10.21859/ijb.1967
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant and Selective Anti-proliferative Effects of the Total Cornicabra Olive Polyphenols on Human Gastric MKN45 Cells

Abstract: Background According to the epidemiological studies, consuming olive products can decrease the incidence of the different types of cancers mostly due to the high anti-oxidant properties of their polyphenolic compounds. Objectives To evaluate the anti-oxidant and anti-proliferative potentials of the olive fruits total polyphenols on the gastric adenocarcinoma MKN45 cells in comparison to the normal Hu02 cells. Materials and Methods The total p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Hosseini-Mazinani et al demonstrated that the polyphenols extracted from olive fruits decreased the growth and viability of the cancerous gastric MKN45 cells through the depletion of intracellular ROS. Similarly, it should be noted that polyphenolic extracts also decreased the ROS level in the normal cells, but the viability of these cells did not significantly change . Moreover, the results shown in Figures C and S5 indicate that GNDs­(S) dramatically inhibited migration.…”
Section: Resultsmentioning
confidence: 70%
“…Hosseini-Mazinani et al demonstrated that the polyphenols extracted from olive fruits decreased the growth and viability of the cancerous gastric MKN45 cells through the depletion of intracellular ROS. Similarly, it should be noted that polyphenolic extracts also decreased the ROS level in the normal cells, but the viability of these cells did not significantly change . Moreover, the results shown in Figures C and S5 indicate that GNDs­(S) dramatically inhibited migration.…”
Section: Resultsmentioning
confidence: 70%
“…It is generally believed that the free radical content of ROS in cells determines the oxidative senescence and death of cells, which is the key factor to promote the process of apoptosis [43][44] . So, we explored the effect of SMF on the total active oxygen content of two ovarian cancer cells within 24 hours.…”
Section: Resultsmentioning
confidence: 99%